Genetic and epigenetic changes in malignant cells of tumors of urogenital organs - Gordiyuk, V.V. (Вiopolymers and Cell, 2010)
More than 90 % of human malignant neoplasms are presented by epithelial tumors. Cancer of urogenital organs is a serious problem because of wide spread of disease and high mortality rates. Tumorogenesis is associated with different defects of genetic apparatus of cells as well as epigenetic factors (DNA methylation disorders, chromatin reorganizations in processes of histones modifications, regulation of gene expression with small non-coding RNAs). In this review we analyzed genetic and epigenetic changes in the urogenital tumors. Більше 90 % злоякісних новоутворень людини становлять пухлини епітеліального походження. Рак органів урогенітальної сфери є значною проблемою через свою розповсюдженість і високий показник смертності. Виникнення пухлин обумовлено різними пошкодженнями генетичного апарату клітини, а також епігенетичними факторами (перебудови хроматину при модифікаціях гістонів, регуляція експресії генів за участі некодуючих малих РНК, порушення процесів метилювання ДНК). В огляді проаналізовано генетичні та епігенетичні зміни при раку органів урогенітальної сфери. Более 90 % злокачественных новообразований у человека имеют эпителиальное происхождение. Рак органов урогенитальной сферы представляет серьезную проблему в связи с его распространенностью и высоким показателем смертности. Образование опухолей обусловлено различными повреждениями генетического аппарата клетки, а также эпигенетическими факторами (перестройки хроматина при модификациях гистонов, регуляция экспрессии генов с участием некодирующих малых РНК, нарушение процессов метилирования ДНК). В обзоре проанализированы генетические и эпигенетические изменения при раке органов урогенитальной сферы.